Investigation of the optimum longitudinal single transverse step location for a high-speed craft - Avci, Ahmet Gultekin; Barlas, Baris (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2023)
One of the crucial aspects of the conceptual design of a stepped planing hull is the prediction of its performance. To improve performance, the prediction of total resistance must become more accurate. In the field of research, both towing tank experiments and numerical analysis may be used to achieve this goal. In this study, experiments were conducted initially to investigate total resistance of a relatively high-speed craft without a transverse step. Later, numerical computations were carried out to validate the experimental results. After it was determined that the test results and CFD methods were in good agreement, the experimental method continued to investigate the resistance properties of the hull with four different configurations to evaluate the optimal longitudinal position of a single transverse step. The ideal longitudinal position of the single transverse step was evaluated based on a similar relatively high-speed hull with a velocity of up to beam Froude number (FrB) 2.56 in this study, focusing on the FrB range between 2.30 and 2.45.
Keywords: planing hull; resistance; stepped hull; transverse step; CFD; PLANING HULLS; PERFORMANCE; BEHAVIOR; WATER; Engineering